Local Community Knowledge About Medicinal Plants in Ethnic Countries on Sumbawa Island - Yuliana, Nila; Daro, Yasinta Aloysia; Fauzi, Muhammad; Astuti, Laily Widya; Utami, Seftiani; Ayu, Ieke Wulan (LPPM STIKes Muhammadiyah Ciamis, 2025)
Background & Objective: Local cultural wisdom on Sumbawa Island related to health is still lacking, in this case it is necessary to get attention from health workers, especially the materials used by the community regarding the safety of the materials used. The objectives of the study were (1) to find out the types of medicinal plants used daily by the people of Sumbawa Island (Sumbawa Ethnic Group, Bima Ethnic Group, Dompu Ethnic Group), (2) to reveal how the people of Sumbawa Island (Sumbawa Ethnic Group, Bima Ethnic Group, Dompu Ethnic Group) obtain and utilize medicinal plants as traditional medicine. Metode: The research approach used in this study is a qualitative approach with an exploratory survey. Result: The results of the interview on medicinal plants originating from Sumbawa are: Babak Pohon Juwet, Babak pohon kemang kuning, Serat Kuku, Mentawer, Babak Tapulet, Kapas Niwang, Sepeda Api, Turi Ungu, Sukun. Conclusion: (1) The types of medicinal plants used daily by the people of Sumbawa Island are 81 types. (2) The way the people of Sumbawa Island obtain and utilize medicinal plants as traditional medicine is obtained from around the house/yard, fields/gardens, and from the forest. The way to process medicinal plants is by boiling the parts of the plant that are utilized, such as tree bark, roots, and leaves, and drinking the water, making a paste to be applied, and drying them to be made into potions.